Keakuratan dan Bias dalam Pemberitaan Indonesia Gelap: (Studi Analisis Isi pada CNNIndonesia.Com) - Nabilah Resaldi; Pandan Yudhapramesti; Gema Nusantara Bakry (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humani..., 2026)
The Indonesia Gelap issue drew considerable public attention because it was closely linked to social criticism of the government and social movements. In this study, a content analysis using quantitative methods was conducted on 83 news articles published by CNN Indonesia from February 17 to 21, 2025. The analysis was based on the news credibility theory proposed by Andrew J. Flanagin and Miriam J. Metzger. The findings were classified as having a very high level of accuracy, with an average rate of 94.4%, including indicators such as consistency between headlines and content, textual accuracy, and the relevance of photographs. Meanwhile, the bias dimension obtained an average percentage of 33.7%, which was categorized as low. The low bias score was reflected in the disproportionate number of sources and quotations presented to the parties involved. These findings indicate that CNNIndonesia.com delivered accurate information, although the reporting had not yet fully achieved balanced coverage of the Indonesia Gelap issue.